HUBUNGAN KEMANDIRIAN BELAJAR DENGAN HASIL BELAJAR IPAS SISWA KELAS IV SEKOLAH DASAR - Anitra, Rien; Sumarli, Sumarli; Yuniastuti, Yuniastuti (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to examine the relationship between learning independence and IPAS learning outcomes among fourth-grade students at SDN 4 Singkawang. The research employed a quantitative correlational design. The population consisted of all fourth-grade students, and total sampling was used as the sampling technique. Data were collected through measurement and indirect communication techniques. The measurement technique involved a multiple-choice test, while indirect communication was conducted using a questionnaire. Data analysis included percentage analysis of learning independence, mean score analysis of learning outcomes, and the Pearson Product Moment correlation test. The results showed that: (1) students’ level of learning independence was categorized as high, with an average percentage of 70%; (2) students’ learning outcomes on the topic “forces in our surroundings” were categorized as moderate, with an average score of 66; and (3) there was a significant relationship between learning independence and learning outcomes, with a correlation coefficient of 0.444 and a significance value of 0.004 < 0.05. In conclusion, the findings indicate a positive and significant relationship between learning independence and IPAS learning outcomes among fourth-grade students.